EKSPLORASI FAKTOR PENGARUH KINERJA KARYAWAN DI RSGM UNIVERSITAS AIRLANGGA - Maulana, Ragil; Hariyanti, Tita; Mulyawan, Indra (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2024)
Exploration of Influencing Factors on Employee Performance at RSGM Universitas Airlangga. Human resources are crucial for the operations of any organization, including hospitals. Employees must exhibit excellent productivity and performance to perform their duties effectively. However, various factors can influence employee performance, necessitating attention from hospital leaders. This research explores factors causing gaps between employee performance and their main duties at RSGM Universitas Airlangga. Using a qualitative approach, data were obtained through in-depth interviews and observations with five participants. The analysis identified 12 factors affecting performance mismatches with duties during working hours. One primary factor causing this gap is employees' lack of respect for their leaders.